Assessing Motor and Cognitive Areas in Older People: Confirmatory Factor Analysis of Portuguese Version of Éxamen Géronto-Psychomoteur. (January 2020) - Morais, Ana; Santos, Sofia; Lebre, Paula; Simões, Celeste
Aging involves changes in psychomotor performance. Few studies are focused on psychomotor skills among older people due, in part, to the inexistence of valid instruments in the field. The purpose of this article is to analyze the factor structure model of the Portuguese version of Exámen Géronto-Psychomoteur . The confirmatory factor analysis was completed in a sample of 497 older persons, aged between 60 and 99 years, with and without dementia (74.4% female; M  = 78.0; standard deviation = 8.6). A baseline one-factor model was compared against 2 three-factor models (first and second order) that were developed based on the previous exploratory factor analysis. Fit indices for the one-factor model were slightly higher when compared with other models; however, the second-order model seems to be more representative of human behavior. The results of this study provide evidence to support a three-factor model: cognition, motor function, and physical aspects.